How teachers’ social-emotional competence affects bullying in rural schools: the chain mediating effect of students’ social-emotional competence and classmate relationship - Ma, Jin; Niu, Xihao (Frontiers in Psychology, 2025)
IntroductionIn recent years, bullying in rural schools has become increasingly prevalent. It is essential to identify the factors that influence bullying in rural schools to better prevent and manage its occurrence.MethodsThis study focuses on Chinese rural students, examining the preventive mechanisms of teachers’ social-emotional competence in mitigating bullying in rural schools. Specifically, the study investigated the mediating role of students’ social-emotional competence and classmate relationship, both individually and as a chain, in this process.ResultsThe findings indicated that teachers’ social-emotional competence does not directly reduce bullying in rural schools. Instead, it exerts its influence through the mediating effect of classmate relationship and the chain mediation of “students’ social-emotional competence-classmate relationship.DiscussionBased on these findings, efforts should focus on improving teachers’ social-emotional competence, enhancing students’ social-emotional competence, and fostering healthier classmate relationship to effectively prevent and control bullying in rural schools.